Assessing the hypotheses against women leadership in African christianity (2013)
Despite the undisputable roles of women as homemakers and nation-builders, many hypotheses had been advanced in support of male chauvinism mostly prevalent in African society. Such discrimination is attributable to two sources; culture and religion. The prejudices, inequalities and injustices suffered by women seem to be deep-rooted. What is even more unfortunate and scandalous is that religion has been and is still being misused to reinforce the oppression and subordination of women. Equally disconcerting is the fact that among the womenfolk themselves there are quite a number who have accepted these conditions as normal and therefore have had no inclination to demand and work for a change. Such women have resigned themselves to an inferior status and sincerely believed that such is their divinely ordered fate. This paper, therefore, is aimed at evaluating the theological, cultural and philosophical hypotheses that serve as roadblocks against women leadership in order to disprove their logical veracity; and to establish that leadership in the church should transcend the factor of gender but be based on God’s prerogative and infinite grace.